Growth of the international economy, 1820-2015 - Graff, Michael; Kenwood, A. G.; Lougheed, A. L. (Abingdon, Oxon ; New York : Routledge, 2014)
Kenwood and Lougheed's classic book has been the benchmark introduction to the development of the global economy for half a century. For this new, fifth edition, Michael Graff has helped bring the story up to date to include events of the early part of the twenty first century - continued globalization, the emergence of China and India as economic powers and the greater role played by business on the international scene. Beginning with the industrial revolution, the book charts the long nineteenth century, the impact of colonialism, the fast pace of technology growth and the impact of global wars. New features to this edition include: a new chapter providing the initial conditions faced by the world economy in 1820, detailing the early years of industrialization and the influence of the slave trade; greater coverage of developing countries, in particular as certain of those countries have risen to prominence and greater influence; and, increased coverage of World Wars I and II and greater coverage of the twentieth century in particular. This edition of "Growth of the International Economy" provides the student with a clear understanding of those factors which have been instrumental in creating the economic environment we face two hundred years after the industrial revolution
Introduction. Prologue : the international economy from the beginnings to 1820 -- The international economy, 1820-1913 -- The First World War and the interwar years -- The Second World War and the post-1945 international economy
Includes bibliographical references (pages 347-358) and index
Keywords: International economic relations -- History; Economic history